RNA binding protein Musashi‐1 directly targets Msi2 and Erh during early testis germ cell development and interacts with IPO5 upon translocation to the nucleus. Issue 7 (17th March 2015) - Sutherland, Jessie M.; Sobinoff, Alexander P.; Fraser, Barbara A.; Redgrove, Kate A.; Davidson, Tara‐Lynne; Siddall, Nicole A.; Koopman, Peter; Hime, Gary R.; McLaughlin, Eileen A.
ABSTRACT: Controlled gene regulation during gamete development is vital for maintaining reproductive potential. During the process of gamete development, male germ cells experience extended periods of inactive transcription despite requirements for continued growth and differentiation. Spermatogenesis therefore provides an ideal model to study the effects of posttranscriptional control on gene regulation. During spermatogenesis posttranscriptional regulation is orchestrated by abundantly expressed RNA‐binding proteins. One such group of RNA‐binding proteins is the Musashi family, previously identified as a critical regulator of testis germ cell development and meiosis in Drosophila and also shown to be vital to sperm development and reproductive potential in the mouse. We focus in depth on the role and function of the vertebrate Musashi ortholog Musashi‐1 (MSI1). Through detailed expression studies and utilizing our novel transgenic Msi1 testis‐specific overexpression model, we have identified 2 unique RNA‐binding targets of MSI1 in spermatogonia, Msi2 and Erh, and have demonstrated a role for MSI1 in translational regulation. We have also provided evidence to suggest that nuclear import protein, IPO5, facilitates the nuclear translocation of MSI1 to the transcriptionally silenced XY chromatin domain in meiotic pachytene spermatocytes, resulting in the release of MSI1 RNA‐binding targets. This firmly establishes MSI1 as a master regulator of posttranscriptional control during early spermatogenesis and highlights the significance of the subcellular localization of RNA binding proteins in relation to their function.—Sutherland, J. M., Sobinoff, A. P., Fraser, B. A., Redgrove, K. A., Davidson, T.‐L., Siddall, N. A., Koopman, P., Hime, G. R., McLaughlin, E. A. RNA binding protein Musashi‐1 directly targets Msi2 and Erh during early testis germ cell development and interacts with IPO5 upon translocation to the nucleus. FASEB J . 29, 2759‐2768 (2015). www.fasebj.org